2019
DOI: 10.30520/tjsosci.511094
|View full text |Cite
|
Sign up to set email alerts
|

Otokrati̇k Ve Katilimci Li̇derli̇k Anlayişinin Örgütsel Vatandaşlik Davranişi Üzeri̇ne Etki̇si̇: Si̇vi̇l Toplum Kuruluşlari Üzeri̇ne Bi̇r Araştirma

Abstract: Bu çalışma otokratik ve katılımcı liderlik anlayışının örgütsel vatandaşlık davranışı üzerine etkisini değerlendirmektedir. Çalışmanın örneklemini sivil toplum kuruluşlarında görev yapmakta olan rastgele örnekleme ile seçilen 280 yönetici ve 130 çalışan oluşturmaktadır. Araştırmada çalışanların vatandaşlık davranışını ölçmek için örgütsel vatandaşlık davranışı ölçeği kullanılmıştır. Araştırmada yöneticilerin liderlik davranışlarını belirlemek için ise "Leadership Opinion Questionnaire" kullanılmıştır. Ölçek "O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…According to Bayyurt and Klç (2017), leaders' authoritarian or democratic views can strongly influence organizational commitment of organizational members. In addition, Altan and Özpehlivan (2019) found that authoritative and participative leadership behaviors have a strong impact on organizational commitment. Based on teachers' perspectives, Inandı et al (2020) examined the relationship between school administrators' leadership styles and change resistance and organizational dissent, and whether administrators' leadership styles predicted change resistance and organizational dissent.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…According to Bayyurt and Klç (2017), leaders' authoritarian or democratic views can strongly influence organizational commitment of organizational members. In addition, Altan and Özpehlivan (2019) found that authoritative and participative leadership behaviors have a strong impact on organizational commitment. Based on teachers' perspectives, Inandı et al (2020) examined the relationship between school administrators' leadership styles and change resistance and organizational dissent, and whether administrators' leadership styles predicted change resistance and organizational dissent.…”
Section: Significance Of the Studymentioning
confidence: 99%